Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 9- Synanthropy and epidemiological vector role of Aedes scapularis in South-Eastern Brazil - Forattini Oswaldo Paulo; Kakitani Iná; Massad Eduardo; Marucci Daniel (Universidade de São Paulo, 1995)
Behaviour comparisons of Aedes scapularis and Ae. serratus are presented. Results were obtained by sampling Aedes adult mosquitoes at several places in the rural anthropic environment in the Ribeira Valley region of S. Paulo State, Brazil. Aedes dominance was shared by those two species, but Ae. scapularis Sshowed a clear tendency to frequent the modified environment, while Ae. serratus was to be found in the more preserved ones, here represented by the vestigial patchy forests. Regarding the open cultivated land and the dwelling environments, Ae. scapularis preponderates. Considering the regional developmental phases, this mosquito showed a remarkable increase in the modified environment differently from Ae. serratus that underwent a considerable decrease in migrating from the forest to the anthropic environment. As a consequence of these results it is reasonable to conclude that Ae. scapularis may be considered as an epidemiologically efficient vector and that it quite probably played this role in the Rocio encephalitis and other arbovirus epidemics.